The Connector's Advantage : 7 Mindsets To Grow Your Influence And Impact - Lederman, Michelle Tillis, 1971-
A leading expert in likability shows that networking is not about the dreaded mixer or cocktail parties-readers will learn how to build meaningful relationships and get results, from retaining top people to increasing profitability.--